Lycenchelys pearcyi Anderson 1995 ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Lycenchelys pearcyi Anderson, 1995. To 38.5 cm (15.2 in) TL. Northern Oregon to southern tip of Baja California. Benthic; depth: 2,663 –3,051 m (8,737 –10,010 ft). All in Anderson (1995). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 181, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...